HOAKS DAN ALQURAN: UPAYA MEMBANGUN PERADABAN KRITIS DALAM MENERIMA BERITA DAN ADAB DALAM BERKOMUNIKASI - Salwa Sofia Wirdiyana (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2019)
This paper seeks to parse the solution to the problem of hoax from the perspective of Quranic interpretation holistically and comprehensively. This study is a qualitative research by reading theÂ relationship (munasabah) between verses aboutÂ hoax in the Holy Quran that are represented by the terms ifk, fasiq, munafiq, murjifun, and tabayyun. After reading the verses related to the term, it was concluded that hoax news can be minimized by critical thinking, having emotional maturity, performing tabayyun, and broadening insight. In addition, the Holy Quran also teaches good communication ethics, namely qaulan sadidan (correct speech), qaulan baligan (good words that leave an imprint on the soul), qaulan maisuran (proper speech), qaulan layyinan (soft words), qaulan kariman (noble words), and qaulan ma'ru fan (good words).Â